Desenvolvimento de bebida de gergelim: estudo de atributos intrínsecos e extrínsecos - Ferreira, Luan Costa (2022)
Sesame is underused in Brazil and because it has excellent amounts of minerals, fibers and unsaturated fats, it becomes a viable alternative as a raw material in the elaboration of new products with health claims. In this way, the objective was to elaborate a drink based on water-soluble sesame extract (EHG) and grape liquid concentrate (CLU), with nutritional and sensorial quality for individuals with or without dietary restrictions, in addition to seeking to relate the non-sensory attributes, such as nutritional and functional claims, with behavioral questions about beverage acceptance. The study comprised two blocks. The first was divided into three stages: 1st) selection of the most accepted soy drink with grape juice (commercial); 2nd) selection of the most accepted sesame drink with liquid grape concentrate; 3rd) comparative analysis, through sensory methods, between the most accepted sample of the 1st and 2nd phase. In the selection of sesame drink and liquid grape concentrate, through experimental planning (combining the levels of the independent variables, EHG and CLU concentration, with the dependent variables, calcium and vitamin C contents in the drinks), the formulations were defined (real value of sesame/CLU for 100mL) F4 (14.28g/45mL), F6 (15.64g/27.5mL) and F8 (10.98g/52.24mL) for sensory analysis as they present satisfactory indices of mineral and vitamin. From the samples and formulations, the acceptance of the attributes of color, aroma, flavor, sweetness, viscosity and overall impression was evaluated, in addition to the onsumption/purchase intention (1st, 2nd and 3rd phase), test of the Ideal for grape flavor and sweetness (2nd phase) and paired comparison between selected samples (3rd phase). In the second, a questionnaire was carried out addressing health and nutrition characteristics, as well as health claims of the drink developed in the first block of studies. Questions about interest in healthy eating and food neophobia were also addressed. It segregated volunteers by gender, age, education and dietary restrictions (health or ideological) for comparative criteria. It selected the formulation of sesame drink “F8”, with 52.24% of CLU and 10.98% of sesame, in obtaining its extract. It also presented 41.79mg of calcium, 128.45mg of phosphorus, 38.63mg of magnesium and 29mg of vitamin C/200mL, with averages of global impression, color and purchase intention of, respectively, 7.52, 7, 80 and 6.07. The mean values of the attributes were included between the terms “neither liked nor disliked” and “liked a lot”. The paired comparison test revealed that there was no preferred vegetable drink. In the second block, information about the beverage's composition, nutritional characteristics and health appeal had a positive impact on consumers' perception of healthiness and nutritional value. The different characteristics of consumers, in general, revealed us with a high interest in healthy eating, but still with neophobic eating behaviors, which suggests the practice of trustworthy marketing aimed at each audience.